QUALIFICATION OF CRIMINAL OFFENCES AND THE CASE LAW OF THE COURT OF JUSTICE OF THE EUROPEAN UNION - Bieliūnas, Egidijus (Teisė, 2017)
This article gives an overview of general condition and certain perspectives of qualification of criminal offences and its theory in relation to the jurisprudence of the EU Court of Justice. It must be admitted, that in terms of the needs of qualification, the abundant jurisprudence of the Court of Justice remains scattered, unpurified, not systematized, therefore insufficiently known, while clearly having a legal potential, significant to perception and application of qualification rules. It is especially visible regarding those standards of qualification which are extracted while combining the rules of national and EU law. Namely because of them, national courts usually refer the preliminary questions to the European Court of Justice and get the needed answers.This article follows the original idea that selection of jurisprudence, organization and presentation may be started by using examples of the rulings of the Court of Justice that illustrate the most important features of qualification as a legal phenomenon. Thus in the beginning the most important, principal structural components of qualification are described, without which at least the so called official qualification is not possible. There are several of them. Firstly, it is socially detrimental offences, without which there is nothing to qualify. Another component – the legal standards, applied while qualifying, by the way, not restricted to the elements of criminal offences, but also including the categories of crimes. Then the subjects, which must or may take operations of qualification, and finally the so called imperative of qualification, describing cases in which qualifying is simply obligatory, in which qualifying is possible depending on circumstances and in which it is prohibited to undertake the qualification actions. In this order a dozen respectively grouped examples of jurisprudence of the Court of Justice are given, which illustrate the possibility to elaborate on the mentioned components of qualification: offences, the standards of their legal evaluation, the subjects engaging in qualification and their obligations and possibilities. For example, common attitude of this Court towards qualification is expressed in Cresson case. The object of a crime is commented in a Lithuanian-originated Babanov case. The terms “the same offense”, “the same facts” are elucidated in the rulings of Mantello and Gasparini e.a. cases. The matter of culpability is commented in Afrasiabi e.a. case, the matter of application of more favourable criminal law – in Paoletti e.a. case. And this is not an exhaustive list of the Court’s judgements significant to qualification. Elucidations on many other matters can be found in the jurisprudence of the Court of Justice, elaborating on the rules of qualification and conditions of their application. This initial analysis of the raised problems, and especially its further development, may be useful for both practice of qualification of criminal offences, as well as its theory.